Exploring the Prospect of Over-the-Top (OTT) Platforms in Bangladesh: A Study on the Users of Khulna District - Saha, Dola Rani; Nath, Chuton Deb (South Asian Journal of Social Sciences and Humanities, 2024)
Introduction: Over-the-Top (OTT) services are developing rapidly in line with the technolo gies’ fast advancement. With the emergence of OTT platforms, the viewing experience has  seen a drastic change. OTT platforms are becoming more attractive to viewers due to their  diversity of content and less advertisements. The main purpose of this study is to understand  the perception and satisfaction of the OTT users of Khulna District. This study also aims to  investigate the OTT video streaming habits and preferences of the users. Methods: This study  is based on a survey method to know the viewer’s engagement, perception and satisfaction  using OTT platforms. Using the convenience sampling technique, an online survey is admin istered to collect feedback from 200 respondents. Results: The findings of this study revealed  that 48.5% people prefer OTT platforms as their major source of entertainment to television or  other video streaming platforms. According to the study, Chorki is the viewer’s most popular  OTT video streaming service. A majority of OTT subscribers thought that the subscription fees  in Bangladesh are higher (42.5%). Censorship is required for semi-nude or sex-based stories in  OTT platforms, according to the majority of the users (47%). Therefore, majority of the sub scribers are not satisfied with the content of these platforms (34%). Most of them (49%) faced  technical difficulties while using OTT platforms. Conclusion: In Bangladesh, OTT platforms have enormous potentials. As the market for these services are expanding swiftly and investors  are recognizing its protectives. This study is expected to help OTT service providers in design ing their contents and services.
Keywords: Over-the-Top (OTT); Engagement; Perception; Satisfaction; Content Variety